(untitled) (World Bulletin of Public Health, 2023)
This review article analyzes the incidence of morbidity and mortality from cardiovascular diseases (CVDs) worldwide, including Uzbekistan. The tasks for decreasing the mortality, morbidity and disability from CVDs before the state cardiology services have also been studied